Deference of Abdication: A Comparison of the Supreme Court of Israel and the United States in Cases Involving Real of Perceived Threats to National Security - Eileen Kaufman (Washington University Global Studies Law Review, 2013)
This Article compares the United States and Israeli Supreme Courts’ very different use of justiciability doctrines and then moves beyond those doctrines to explore the impact of actual decisions on policies undertaken in the name of national security. Part II describes the articulated philosophies of the two courts regarding the role of judicial review in cases involving national security. This part explores three justiciability doctrines—the political question doctrine, standing requirements, and the state secrets privilege—and compares the two courts’ declared positions with respect to those doctrines in cases dealing with foreign affairs. It also analyzes the two courts’ articulated philosophies regarding the scope of judicial review in cases implicating military decisions. Part III of the article moves away from the courts’ rhetorical stances on questions of justiciability and judicial review and examines and compares decisions of the two courts in cases that pit national security against individual liberties. This part looks at cases challenging practices including targeted killings, torture, administrative detention, and other actions undertaken in the name of national security. Part IV concludes that (a) the two courts have the institutional capability to resolve challenges to national security policies; (b) adherence to non-justiciability doctrines like the political question doctrine amounts to an abdication of the judicial role; and (c) the availability of judicial review has an actual effect on governmental policy and military practice.
Keywords: supreme court; Israel; Supreme Court of the United States; Supreme Court of Israel; national security